Review of ad‐hoc on‐demand distance vector protocol and its swarm intelligent variants for Mobile Ad‐hoc NETwork. Issue 5 (1st September 2017) - Jinil Persis, Devarajan; Paul Robert, T.
Abstract : Mobile Ad‐hoc NETwork (MANET) is a rapidly changing network having mobile nodes. The wireless links connecting a node pair are unreliable due to the mobility of nodes; thereby MANET is subjected to frequent link failures that subsequently lead to route failure. It is required for the routing algorithms to determine routes enduring connectivity providing uninterrupted data transmission without compromising quality of service and load balancing. Ad‐hoc on‐demand distance vector (AODV) routing protocol is predominantly used in MANET for making routing decisions because of its performance in terms of delay, throughput, packet delivery ratio and number of hops when compared to other protocols in the literature. However, this protocol often converges to less reliable routes leading to high control overhead and packet loss. In this study, a multi‐objective AODV algorithm is proposed to consider distance, cost, delay, load and reliability as routing metrics. Also modified versions of AODV protocol by applying ant colony optimisation, bee colony optimisation and firefly algorithms have been proposed and the results are presented.